2001
DOI: 10.1046/j.1440-1819.2001.00829.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of junior high school students’ sleep habit and lifestyle in Okinawa

Abstract: A survey was made of the sleep and lifestyle activity patterns of 3754 students from 14 different junior high schools on Okinawa Island. The survey showed that bedtimes became progressively and significantly later as students ascended to higher grades, resulting in adolescent sleep debt. The later adolescents retired to sleep, there appeared significantly greater numbers suffering from insufficient sleep, who found difficulty in waking up, who arose later in the mornings, and who failed to eat breakfast. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 1 publication
7
29
0
1
Order By: Relevance
“…It was common for bedtime to be delayed for adolescents while rise time remained the same [18]. The findings of this study were similar to previous reports in secondary school students.…”
Section: Discussionsupporting
confidence: 90%
“…It was common for bedtime to be delayed for adolescents while rise time remained the same [18]. The findings of this study were similar to previous reports in secondary school students.…”
Section: Discussionsupporting
confidence: 90%
“…A significant association between SHSB and late dinner suggests that those persons skipping breakfast habitually, rather than intentionally as part of a diet, possibly have a nocturnal lifestyle [19,20]. Indeed, a late dinner just before sleeping may impair postprandial glucose metabolism and food digestion, and it may lead to prolonged elevated FPG and poor appetite in the morning.…”
Section: Discussionmentioning
confidence: 99%
“…These results mean that dinner at a later time was related to delayed bedtime in the LF group, and eating breakfast was associated with an earlier bedtime in the LA group. Many studies have suggested a relationship between meal habits and sleep pattern and/or sleep quality (e.g., Arakawa et al 2001;Tanaka et al 2002;Nakade et al 2009). Moreover, studies on mammals such as rodents suggest that the timing of food intake may entrain the internal biological clock system either directly or indirectly through other neural or peripheral systems (Mendoza 2007).…”
Section: Discussionmentioning
confidence: 99%